Construction of Sn3O4/g-C3N4 Composite with Enhanced Photocatalytic Activities Under Visible Light Irradiation - Hoang Huong, Vu (VNU Journal of Science: Mathematics - Physics, 2023)
The Sn 3 O 4 /g-C 3 N 4 composites were produced by an annealing mixture of g-C 3 N 4 and Sn 3 O 4 , which were prepared by calcining urea and hydrothermally treating of SnCl 2 solution, respectively. Chacterization of the samples was investigated by powder X-ray diffraction (XRD), Scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), Photoluminescence (PL) and UV-Vis spectra. Studying the degradation of Rhodamine B (RhB) in the presence of visible light showed that the combination of Sn 3 O 4 and g-C 3 N 4 has an enhanced ability in the photocatalysis in comparison with the individual components. From kinetic investigations of RhB degradation, it is found that the SCN25 catalyst has the highest rate constant of 18.14 (min -1 x 10 3 ), which was about 11.4 times larger than that of pure g-C 3 N 4 . It is possible to explain the improved photocatalytic activity of Sn 3 O 4 /g-C 3 N 4 composites by using the Z-scheme pathway.